Die Homilien und Fragmente zum Hohelied - Origenes 185-254 (Werke mit deutscher Übersetzung., 2016)
Hieronymus claimed that Origen had even surpassed himself in his Commentary on the Song of Songs. With these words of praise, Hieronymus spread the good word about the Christian genius from Alexandria and, for this purpose, translated two of Origen’s homilies on the Biblical song of love into Latin. Besides Rufinus’s Latin translation, only a number of small fragments of this presentation of the Song of Songs have survived.